Development of Scrapbook Learning Media for Pancasila Education in Grade III at SDN 09 Sitiung - Muhammad Sukron; Antik Estika Hader; Nabila Yasmin Azzahra (The Future of Education Journal, 2026)
This research was motivated by several problems in learning. Lack of student motivation is caused by learning methods that only use stationery as a medium, resulting in students having difficulty understanding what the teacher explains. Lack of varied learning media is also caused by a lack of learning facilities. It turns out that in the Pancasila subject, students appear unmotivated during each learning process, especially for Pancasila material, because they lack the drive or enthusiasm to learn. This study used the Research and Development (R&D) method. The ADDIE model consists of five stages: analysis, design, development, implementation, and evaluation. The validation results for the scrapbook learning media development, assessed by three expert validators, were: 97% valid with material validation, 73% valid with minor revisions, and 75% valid with media validation. Data analysis of the teacher response questionnaire, scored 100% by one teacher, was categorized as very practical, and data analysis of the student response questionnaire, scored an average of 98%, categorized as very practical. The effectiveness of the learning assessment for third-grade students was categorized as 89% complete.